2000
DOI: 10.1111/j.1744-7348.2000.tb00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and relative humidity effects on egg and nymphal development of Aceria tulipae (K.) (Acari: Eriophyidae) on garlic leaves (Allium sativum L.)

Abstract: Aceria tulipae (K.) is responsible for important crop losses of garlic in all production areas around the world. However, very little is known about its development in relation to temperature and relative humidity (r.h). Laboratory rearings from egg to adult stage were done on pieces of the apical part of young garlic leaves. These leaf pieces were placed in aluminium dishes floating on water or put on a solid hygroscopic salt in closed plastic trays. Rearing done in dark incubators at constant temperatures (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
(5 reference statements)
1
14
0
1
Order By: Relevance
“…In preliminary observations, humidity saturation impaired mite movement and reduced survival. Other authors also avoided 100% relative humidity, and have reported a negative impact on egg hatchability or mite survival due to condensation (Perring et al 1984, Frost 1997, Courtin et al 2000. The limitations of a saturated microenvironment may influence the wheat curl mite survival and could be a factor in the mites increased prevalence throughout the more arid western Great Plains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preliminary observations, humidity saturation impaired mite movement and reduced survival. Other authors also avoided 100% relative humidity, and have reported a negative impact on egg hatchability or mite survival due to condensation (Perring et al 1984, Frost 1997, Courtin et al 2000. The limitations of a saturated microenvironment may influence the wheat curl mite survival and could be a factor in the mites increased prevalence throughout the more arid western Great Plains.…”
Section: Discussionmentioning
confidence: 99%
“…In poikilotherms, survival and movement are heavily influenced by temperature as this affects the rate of metabolic processes and by relative humidity as this influences their water balance (Hoffmann and Blows 1994, Chown et al 2011, Melo et al 2014). Temperature and relative humidity are reported to influence survival, development, and reproduction of mites (Perring et al 1984, Courtin et al 2000. Several authors have reported that wheat curl mite survive for a short period without a living host (Slykhuis 1955, Nault and Styer 1969, Jiang et al 2005, Wegulo et al 2008); however, no published studies have demonstrated the limits of these effects for the wheat curl mite.…”
mentioning
confidence: 99%
“…The procedure developed by De Silva and Fernando (2008) to successfully mass rear Aceria guerreronis Keifer on embryo culture seedlings for up to 5 weeks offers promise for rearing of species strictly associated with young and meristematic tissues. Rearing was also indirectly handled in a few others studies (Courtin et al 2000;Schwoebel and Beiderbeck 2000;Gondim and de Moraes 2003;Skare et al 2003;Ansaloni and Perring 2004;Skoracka and Kuczyński 2004;Witt 2004;Britto et al 2008), resulting in successful multiplication of eriophyoids dedicated to various subsequent biological investigations.…”
Section: Rearing Techniquesmentioning
confidence: 96%
“…A. hystrix, Aceria oleae (Nalepa), Tegolophus hassani (Keifer), Aculops lycopersici (Tryon), and A. guerreronis), as well as species attacking weeds [F. perrepae] are capable of rapid population increase under optimal environmental conditions (Ramarethinam and Loganathan 2000;Haque and Kawai 2003;Skoracka and Kuczyński 2004;Abou-Awad et al 2005;Ozman and Goolsby 2005). In addition, temperature and humidity requirements for development and reproduction of A. lycopersici, A tulipae, and A. guerreronis have been carried out (Courtin et al 2000;Haque and Kawai 2003;Ansaloni and Perring 2004;Xu et al 2006). Information on life-history parameters is essential for understanding the population dynamics of species.…”
Section: Physiologymentioning
confidence: 98%
“…Mites which attack garlic in storage include Aceria tulipae. Courtin et al (2000) studied its biology to identify the environmental conditions which most favour the pest. They found that a temperature of 25°C was ideal for rapid multiplication.…”
Section: Garlic Pathogens and Pests In Storagementioning
confidence: 99%